Delay Time and Preservation Method in Urine Epithelial Examination: Waktu Penundaan dan Metode Penyimpanan dalam Pemeriksaan Epitel Urin - Suci Purwati; Puspitasari (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Urinalysis is an essential diagnostic tool for detecting metabolic and urinary tract disorders, including complications in diabetes mellitus patients. Specific Background: In diabetes mellitus, urinary tract infections frequently occur and are associated with epithelial cell changes in urine sediment. Knowledge Gap: However, limited evidence exists regarding the effect of delayed examination and preservation methods on urine epithelial integrity. Aims: This study aims to analyze the effect of delay time and preservation methods on urine epithelial examination in diabetes mellitus patients. Results: Using an analytical experimental approach with 30 urine samples, the findings show that delayed examination at 4 and 5 hours leads to a decrease in epithelial cell count and morphological changes. Storage at 4°C demonstrates better preservation compared to the addition of 10% formaldehyde, although both methods show significant differences based on the Friedman test. Novelty: This study highlights the comparative outcomes of cold storage and formaldehyde preservation under delayed conditions in diabetic patient samples. Implications: The findings emphasize the importance of proper sample handling and timely examination to maintain the accuracy of urinalysis results in clinical laboratory practice. Keywords: Urinalysis, Epithelial Cells, Delay Time, Preservation Method, Diabetes Mellitus Key Findings Highlights Reduced cell counts observed with prolonged examination delay Cold storage maintained structural characteristics more consistently Preservative addition associated with morphological alteration